Donne sul filo della 'soglia'. Aves exóticas. Cinco cuentos con mujeres raras de Reina Roffé (Altre Modernità, 2014)
The essay analyzes the collection Aves exóticas (2004 and 2011), of Argentinean writer Reina Roffé, and emphasizes how the limen’s figure, present in each short story, corresponds to various representations of exile.
Keywords: Esilio; Frontiera; Transculturazione